Fragile: Handle with Care - Rubio, Hosanna (East Carolina University, 2017)
Memory has always been dearly held in my family, and easily lost. I watched as my loved ones surrounded themselves with objects that acted as physical anchors to the full lives they had lived, the places they had been, and the things that were important to them. This experience heightened my desire to document, to create a catalogue of my own that will allow me to capture my life in this moment. Fragile: Handle with Care is a body of work consisting of jewelry and sculptures that explore significant issues such as mortality, religion, and gender. Creating layered, detailed pieces allows me to find balance in the chaotic, to attempt to exert control over the uncontrollable aspects of my life and in the world at large. Petra Ahde-Deal asserts that jewelry is not only for adornment, but that it at times can be used to ease moments of change. In her words, "transitional jewelry can function as healing devices in reconstructing the self after personal crises." (91) My work combines traditional metalsmithing techniques such as enameling and casting with newer technologies like digital manipulation to create intricate pieces that serve as a platform to explore this recreation of identity. My experiences are not universal, but I hope to inspire an atmosphere of dialogue with my work to show that sometimes moments of pain and tragedy can offer us the greatest opportunities for beauty and transformation.
Keywords: Memory in art; Nostalgia in art; Healing in art; Jewelry; Sculpture